Mapping Of Soil Nutrient Status Rice Field IP-200 and IP-300 in Desa Baru Kecamatan Batang Kuis Kabupaten Deli Serdang - Fitra Rizki Aghita Purba; Razali Razali; Benny Hidayat (Jurnal Agroekoteknologi, 2018)
ABSTRACT The purpose of this research to mapping and compare Soil nutrient status cause by increased Rice Field Cultivation Index in Desa Baru Kecamatan Batang Kuis Kabupaten Deli Serdang. The research was conducted in Desa Baru Kecamatan Batang Kuis Kabupaten Deli Serdang, Research and Technology of Laboratory Agriculture Faculty USU and Research Laboratory PT. Socfindo is done from October 2016 to March 2017, using the Free Survey Grid method with level of  a scale is 1: 10,000 (1 sample representing 1 ha of paddy field). Parameters observed included C-Organic Soil (Walkley and Black), N-Total Soil (Kjedahl Method), P2O5 (25% HCl Extract), K2O ( 25% HCl Extract). The results from Laboratory analysis were grouped using the Land Research Center's criteria in 1983. Mapping and comparing the soil nutrient status (C-organik, N, P2O5, K2O) were done using Geographic Information System (GIS) with Interpolation technique. The result showed there was decreased of C-Organic soil, Nitrogen and K2O due to by the increased of Rice Field (IP), no decrease of nutrient status P2O5 due to by the increase of Rice Field Cultivation.             Keywords: Crop Index (IP), Rice Field, Geographic Information System (GIS).